Health economic evaluation of a serum-based blood test for brain tumour diagnosis: exploration of two clinical scenarios. Issue 5 (24th May 2018) - Gray, Ewan; Butler, Holly J; Board, Ruth; Brennan, Paul M; Chalmers, Anthony J; Dawson, Timothy; Goodden, John; Hamilton, Willie; Hegarty, Mark G; James, Allan; Jenkinson, Michael D; Kernick, David; et al.
Abstract : Objectives: To determine the potential costs and health benefits of a serum-based spectroscopic triage tool for brain tumours, which could be developed to reduce diagnostic delays in the current clinical pathway. Design: A model-based health pre-trial economic assessment. Decision tree models were constructed based on simplified diagnostic pathways. Models were populated with parameters identified from rapid reviews of the literature and clinical expert opinion. Setting: Explored as a test in both primary and secondary care (neuroimaging) in the UK health service, as well as application to the USA. Participants: Calculations based on an initial cohort of 10 000 patients. In primary care, it is estimated that the volume of tests would approach 75 000 per annum. The volume of tests in secondary care is estimated at 53 000 per annum. Main outcome measures: The primary outcome measure was quality-adjusted life-years (QALY), which were employed to derive incremental cost-effectiveness ratios (ICER) in a cost-effectiveness analysis. Results: Results indicate that using a blood-based spectroscopic test in both scenarios has the potential to be highly cost-effective in a health technology assessment agency decision-making process, as ICERs were well below standard threshold values of £20 000–£30 000 per QALY. This test may be cost-effective in both scenarios with test sensitivities and specificities as low as 80%; however, the price of the test would need to be lower (less than approximately £40). Conclusion: Use of this test as triage tool in primary care has the potential to be both more effective and cost saving for the health service. In secondary care, this test would also be deemed more effective than the current diagnostic pathway.